Tờ trình tóm tắt về thí điểm cơ chế, chính sách đặc thù phát triển thành phố Hồ Chí Minh - Chính phủ (2017)
Tờ trình tóm tắt về thí điểm cơ chế, chính sách đặc thù phát triển thành phố Hồ Chí Minh (Số: 531/TTr-CP) ngày 08/11/2017.